Does nest occupancy by birds influence the microbial composition? - Xin, Jiajia; Cao, Heqin; Bao, Xiaoyang; Hu, Canshi (Frontiers in Microbiology, 2023)
Nest microbiota plays an important role in the breeding and development of birds, which can not only provide protection to bird hosts, but also negatively affect the host. At present, it has not been well studied whether nesting affects the composition of the microbes in the nests. For this reason, this study hanged artificial nest boxes to simulate the natural nest scenario and combined 16S rRNA and ITS high-throughput sequencing technology to further study the differences in microbial composition and richness between used nests and control nests of Japanese tit (Parus minor). The results showed that the used nests and control nests bacteria showed significant differences at the phylum level (P<0.05), the main predominant bacteria in used nests were Proteobacteria (51.37%), Actinobacteria (29.72%), Bacteroidetes (6.59%) and Firmicutes (3.82%), while the main predominant bacteria in control nests were Proteobacteria (93.70%), Bacteroidetes (2.33%) and Acidobacteria (2.06%). Both used nests and control nests showed similar fungi at the phylum, which consisted mainly of Ascomycota and Basidiomycota, although significant differences were found in their relative abundances between both groups. The results of Alpha diversity analysis showed significant differences in bacteria between the two groups and not in fungi. However, the Beta diversity analysis showed significant differences between both bacteria and fungi. In summary, our results showed that there were more beneficial microbiota in the used nests and less pathogenic microbiota. Therefore, we speculate that birds will change the characteristics of the nest microbial composition in the process of nest breeding to ensure their smooth reproductive development.